Implementation Of Internet Of Things (Iot) Based Lecture Schedule In Building G Floor 3 Padang State Polytechnic - Wulandari, Anggelina; Lifwarda, Lifwarda; Firdaus (International Journal of Wireless And Multimedia Communications, 2024)
The internet of things-based lecture schedule aims to improve the efficiency and effectiveness of time management. Thus, students, lecturers, and staff can know the time change so that they can prevent delays. By using Arduino Uno as the main component microcontroller, RTC as a clock module that calculates the time that will be displayed on the LCD. Bell and Speaker will sound when the clock on the RTC is the same as the inputted schedule clock, then sent to IoT via the ESP01 wifi module. This tool can also be used as a medium for delivering information because it is equipped with a mic. The RTC in this tool successfully calculates the time according to real time where the Bell and Speaker can work on time according to the schedule. When the bell sounds the measured voltage is 225 volts while the speaker is 2 volts. This tool has also been connected to ThingSpeak using the ESP01 wifi module.